PERIFRASA DALAM RETORIKA PRESIDEN MAHMOUD ABBAS (STUDI BALAGHAH PERSPEKTIF POLITIK) - Muhammad Bachrul Ulum (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2021)
The strategy in rhetoric is a crucial ability that politicians must possess so that what is conveyed can be accepted by the public entirely and widely. This study will discuss how Palestinian President Mahmoud Abbas devised a rhetorical strategy using Periphrases in his Speech at the 75th United Nations General Assembly to transfer his political message to the world. Precisely a few days after the announcement of the agreement to normalize diplomatic relations of the United Arab Emirates (UAE) and Bahrain with Israel. Mahmoud Abbas is an accomplished diplomat who has succeeded in bringing Palestine to progressive achievements to gain recognition of sovereignty and political support from other countries. This study uses a qualitative method with a literature study model. The data collection method used the listening method with the free-talk listening technique (SBC) and the note-taking technique as an advanced method. The results of this study are that Mahmoud Abbas pours many political messages in the phrases he used when delivering the Speech, which was stated through Ithnab's functions based on social facts in Palestine.Keywords : Periphrase, rhetoric, politic, Mahmoud Abbas, Palestine